QUALITY EDUCATION IN UNDERSERVED AREAS: IMPLEMENTING DEEP LEARNING FOR MADRASAH TEACHERS IN SEMANU DISTRICT - Stephen Taylor; M. Mahbubi; Raudlatun Raudlatun; Ali Anhar Syi'bul Huda (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2026)
This study explores the implementation of deep learning in madrasah classrooms in Semanu, Gunung Kidul, Yogyakarta, focusing on the villages of Nglegi and Pacarejo. The research aims to assess how deep learning principles can be integrated into the teaching practices of teachers in these rural areas, examining the challenges and opportunities for its application. Using a qualitative case study approach, data were collected through semi-structured interviews with 15-20 madrasah teachers, classroom observations, and document analysis. The findings reveal that while many teachers show a willingness to adopt deep learning, their understanding of the concept remains limited. Teachers predominantly rely on traditional, teacher-centered methods, with insufficient knowledge of how to integrate deep learning effectively. Key challenges include the lack of access to technology, limited professional development opportunities, and a rigid national curriculum that prioritizes content delivery over critical thinking and problem-solving. Despite these challenges, teachers expressed interest in enhancing their teaching practices and identified technology and training as essential for adopting deep learning. The study concludes that to effectively implement deep learning in rural areas, there is a need for increased access to technology, context-specific professional development, and curriculum reforms that allow for more flexible and reflective learning. By addressing these challenges, the quality of education in Semanu could significantly improve, preparing students for future challenges